UJI AKTIVITAS ANTIBAKTERI KRIM ASAM LAURAT TERHADAP Staphylococcus aureus ATCC 25923 DAN Pseudomonas aeruginosa ATCC 27853 - Evi Sulastri; Mappiratu Mappiratu; Annisa Kartika Sari (Universitas Tadulako, 2016)
Lauric acid is a saturated fatty acid found in fatty/vegetable oils, especially in palm oil. Lauric acid was reported to posses antiviral and antibacterial property. This study aims to determine the effect of the concentration variance of lauric acid in cream on the stability of the cream physical quality and antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa. In this research, lauric acid concentration in cream was varied in 10%, 20%, and 30% and then tested for antibacterial activity using hole plate technique. The results of the evaluation of lauric acid cream preparation of Formula 1, Formula 2 and Formula 3 showed that the organoleptic and homogeneity tests of all formula was no difference during storage time, but the result of pH, viscosity, and dispersive power of all formula has difference during storage time (28 days). The antibacterial test results showed that the highest inhibition diameter was found in the use of lauric acid concentration of 30% for S.aureus (21.589 mm ± 0.18) and P.aeruginosa (14.25 ± 0.37 mm). Based on statistical analysis of the cream produced from the three concentrations of lauric acid, they were not stable because there are significant differences in pH, viscosity, and dispersive power during storage time (28 days). Keywords: lauric acid, antibacterial cream, Staphylococcus aureus, Pseudomonas aeruginosa.